Effect of insertion layer on electrode properties in magnetic tunnel junctions with a zero-moment half-metal - Stamenov, Plamen; Rode, Karsten; Coey, John; Venkatesan, Munuswamy; Atcheson, Gwenael (My University, 2019)
Due to its negligible spontaneous magnetization, high spin polarization and giant perpendicular magnetic anisotropy, Mn2RuxGa (MRG) is an ideal candidate as an oscillating layer in THz spin-transfertorque nano-oscillators. Here, the efect of ultrathin Al and Ta difusion barriers between MRG and MgO in perpendicular magnetic tunnel junctions is investigated and compared to devices with a bare MRG/MgO interface. Both the compensation temperature, Tcomp, of the electrode and the tunneling magnetoresistance (TMR) of the device are highly sensitive to the choice and thickness of the insertion layer used. High-resolution transmission electron microscopy, as well as analysis of the TMR, its bias dependence, and the resistance-area product allow us to compare the devices from a structural and electrical point of view. Al insertion leads to the formation of thicker efective barriers and gives the highest TMR, at the cost of a reduced Tcomp. Ta is the superior difusion barrier which retains Tcomp, however, it also leads to a much lower TMR on account of the short spin difusion length which reduces the tunneling spin polarization. The study shows that fne engineering of the Mn2RuxGa/barrier interface to improve the TMR amplitude is feasible.
PUBLISHED
Keywords: Magetization; Magnetic tunnel junctions; Mn2RuxGa (MRG); FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics